Pengaruh Pupuk Organik Cair Biji Karet dan Biochar Cangkang Biji Karet Terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) - Supriyanto, Bambang; Darma, Suria; Ramayana, Syamad; Sarwono, Rahmaan (Mulawarman University, 2025)
The productivity of cayenne pepper plants has decreased. This is due to the availability of nutrients on cultivated land decreasing so that the use of rubber plantation waste can be used as an ingredient in making liquid organic fertilizer and biochar to increase the growth and yield of cayenne pepper plants. This study was conducted to determine the interaction of giving liquid organic fertilizer of rubber seeds with rubber seed shell biochar, getting the best concentration of liquid organic fertilizer of rubber seeds and getting the best dose of biochar of rubber seed shells. The research was conducted from December 2022 to June 2023 at Sumber Rejo Village, Sekolaq Darat District, West Kutai Regency. The research used a Randomized Block Design with two factors and five replications. The first factor was rubber seed liquid organic fertilizer and the second factor was rubber seed shell biochar. The data obtained were analyzed using analysis of variance and if it showed a significant effect, it was continued by using Least Significant Different (LSD) at the 5% level. The treatment of rubber seed liquid organic fertilizer with a concentration of 200 mL L-1 solution gives the fastest first flower out age of 39.20 days after transplanting and gives the fastest first fruit formation age of 44.60 days after transplanting.The treatment of rubber seed liquid organic fertilizer with a concentration of 300 mL L-1 solution gave the second harvest with the highest number of 23.55 fruits and gave the best fresh weight of cayenne pepper which was 37.30 g. The results showed that the interaction of the application of liquid organic fertilizer of rubber seeds with rubber seed shell biochar gave a significantly different effect on all observation parameters. liquid organic fertilizer of rubber seeds gave a significantly different effect on the observation parameters of the age of the first flower out, the age of the first fruit formed, the number of second harvest and the weight of fresh fruit of the second harvest. The use of rubber seed shell biochar gives a significantly different effect on all observation parameters. Keywords: rubber seed shell biochar, cayenne pepper, rubber seed liquid organic fertilizer.